Effects of photo regime on the timing of male responses to sex pheromones in male Cnaphalocrocis medinalis (Lepidoptera: Crambidae) - Kawazu, K.; Adati, T.; Tatsuki, S. (2003)
We examined the effect of moth age and photoregime on the timing of male response to sex pheromones in male Cnaphalocrocis medinalis. The responsiveness of males varied with age, increasing up to 3-days and then remaining constant to 7-days. In male responses to the pheromone throughout the scotophase under five different photoregimes, it was shown that the time to reach the maximal response level after lights-off was rather constant (ca. 4 h), regardless of the duration of the scotophase in a range from 6 to 18 h. The maximal response level in every case appeared to be maintained until the end of the scotophase. Furthermore, in the experiment involving 63 h shifts of lights-off or lights-on timing from the usual 15L:9D, the male responsiveness increased within 4 h after lights-off, and the maximal level extended throughout the remaining dark period. These results suggest that, at least under the present experimental conditions, only lights-off and lights-on cues are critical for the timing of the increase and decrease in responsiveness. No responsiveness was observed under light conditions, showing that light inhibits the responsiveness of males to sex pheromones.